Perlindungan Hukum Terhadap Produk Usaha Mikro, Kecil, Menengah Di Kota Madiun Melalui Pendaftaran Hak Merek - Kenes Herlambang; Andina Elok Puri Maharani (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2024)
Usaha Mikro, Kecil dan Menengah (UMKM) has an important and strategic role in national economic development. The importance of the legality of brand rights as an effort to legally protect UMKM, and the creation of a guide on procedures for processing legality documents for brand rights for UMKM. This activity is important because law is an inseparable part of human existence. This is in line with the adage ubi societas ibi ius which means where there are humans, there is law. Remembering that the legality of trademark rights is a legal umbrella for a business entity. However, there are still quite a lot of UMKM industry players in Madiun City who have not registered their trademarks due to limited capital and lack of understanding of the benefits of trademark registration for the UMKM industry. Thus, UMKM that do not register their trademarks do not receive legal protection, because a trademark will receive legal protection if the trademark has been registered. Thus, a policy is needed that regulates the UMKMindustry in Madiun City to obtain legal protection for its trademarks. So this research will examine the legality of brand rights as an effort to legally protect UMKM in Madiun City and how to create a guide on procedures for processing legality documents for brand rights for UMKM in Madiun City. This research uses normative research methods.